Synthesis and characterization of polyurethane-grafted single-walled carbon nanotubes via click chemistry - Rana, Sravendra; Cho, Jae Whan; Kumar, Indresh (Journal of Nanoscience and Nanotechnology, 2010)
Polyurethane (PU)-grafted carbon nanotubes were synthesized by the coupling of alkyne moiety decorated single walled carbon nanotube (SWCNT) with azide moiety containing PU using Cu(I) catalyzed Huisgen [3 + 2] cycloaddition click chemistry. The azide moiety containing poly(E-caprolactone)diol was synthesized by ring-opening polymerization and further used for PU synthesis. Alkyne-functionalizion of SWCNT was completed by the reaction of p-aminophenyl propargyl ether with SWCNT using a solvent free diazotization procedure. Nuclear magnetic resonance, Fourier transform infrared, and Raman spectroscopic measurements confirmed the functionalization of SWCNT. Scanning electron microscopy and transmission electron microscopy images showed an excellent dispersion of SWCNTs, and specially debundling of SWCNTs could be observed due to polymer assisted dispersion. A quantitative grafting was successfully achieved even at high content of functional groups.
Keywords: Carbon nanotubes; Click chemistry; dispersion; polyurethane